The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/jsid.148
|View full text |Cite
|
Sign up to set email alerts
|

Carbonation reaction of (Ca, Mg)O protective layer on plasma display panel

Abstract: We have been applying a low discharge voltage (Ca, Mg)O protective layer to plasma display panels to reduce their power consumption. However, (Ca, Mg)O is highly reactive with CO2, and the resulting carbonate formation during high‐temperature panel sealing in air impairs the low discharge voltage characteristic. We investigated the mechanism of the carbonation reaction that occurs on a (Ca, Mg)O surface during annealing in air at 450°C and found that the CO2 diffuses through the formed CaCO3 layer and that a (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The analysis of the depth profiles of photoelectron signals from carbon has revealed that the depth of the presence of carbon from the surface is related to the discharge voltage for a (Ca,Mg)O protective layer with different CaO concentrations. 42) We have directly demonstrated that no carbonation of the (Mg,Ca)O protective layer in the panels occurs at Mg sites, but that it occurs predominantly at Ca sites; the carbonation ratio is clearly related to discharge voltage, even at the same CaO concentration.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The analysis of the depth profiles of photoelectron signals from carbon has revealed that the depth of the presence of carbon from the surface is related to the discharge voltage for a (Ca,Mg)O protective layer with different CaO concentrations. 42) We have directly demonstrated that no carbonation of the (Mg,Ca)O protective layer in the panels occurs at Mg sites, but that it occurs predominantly at Ca sites; the carbonation ratio is clearly related to discharge voltage, even at the same CaO concentration.…”
Section: Resultsmentioning
confidence: 71%
“…The material with the highest potential as a higher-γ protective layer is (Mg,Ca)O. [25][26][27][28][29][30] (Mg,Ca)O is relatively stable compared with the other materials described above because it is MgO-based. Many groups report that low discharge voltages are obtained relative stably with a (Mg,Ca)O protective layer.…”
Section: Introductionmentioning
confidence: 99%